2020
DOI: 10.1186/s41182-020-00266-z
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of loss to follow-up among HIV-positive adults in northwest Ethiopia: a retrospective cohort study

Abstract: Background Despite the rapid expansion of antiretroviral therapy services, ‘loss to follow-up’ is a significant public health concern globally. Loss to follow-up of individuals from ART has a countless negative impact on the treatment outcomes. There is, however, limited information about the incidence and predictors of loss to follow-up in our study area. Thus, this study aimed to determine the incidence rate and predictors of loss to follow-up among adult HIV patients on ART. Methods A retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 21 publications
(34 reference statements)
7
21
3
Order By: Relevance
“…In this study, 46 (9.1%) adult HIV patients experienced loss to follow-up and the overall incidence rate of loss to follow-up was 5.3 (95% CI: 3.9-7.1) per 100 person-years of observation (PYs). This finding is consistent with the study conducted in Debre Markos, Ethiopia, which reported 3.7 per 100 person-years [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, 46 (9.1%) adult HIV patients experienced loss to follow-up and the overall incidence rate of loss to follow-up was 5.3 (95% CI: 3.9-7.1) per 100 person-years of observation (PYs). This finding is consistent with the study conducted in Debre Markos, Ethiopia, which reported 3.7 per 100 person-years [ 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…This might be because patients from the rural area may face a problem of accessibility or distance from treatment centers, transport-related costs, low level of awareness on the benefit and risk related to the adherence of treatment, and social stigma related to a disease HIV/AIDS. In contrary to this finding, a study done in Debre Markos, Ethiopia, reported that the risk of LTFU among rural residents was reduced by 40% when compared with urban residents [ 22 ]. The possible reason given is that study were patients coming from rural areas preferred to have ART follow-up in the nearby hospitals; this is because rural residents are stable or permanent residents compared to urban residents and due to the scarcity of money; they may not use the self-referral system to other healthcare institutions when compared to urban residents [ 22 ].…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The median age at ART initiation was 34 years (interquartile range [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. The female/male sex ratio was 2.19/1.…”
Section: Resultsmentioning
confidence: 99%